2014
DOI: 10.2967/jnumed.114.145326
|View full text |Cite
|
Sign up to set email alerts
|

Prospective International Cohort Study Demonstrates Inability of Interim PET to Predict Treatment Failure in Diffuse Large B-Cell Lymphoma

Abstract: The International Atomic Energy Agency sponsored a large, multinational, prospective study to further define PET for risk stratification of diffuse large B-cell lymphoma and to test the hypothesis that international biological diversity or diversity of healthcare systems may influence the kinetics of treatment response as assessed by interim PET (I-PET). Methods: Cancer centers in Brazil, Chile, Hungary, India, Italy, the Philippines, South Korea, and Thailand followed a common protocol based on treatment with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(53 citation statements)
references
References 31 publications
1
50
1
Order By: Relevance
“…This method and markers are accepted as gold standard and reliable for the subclassification. These patients were a subset of the cohort of a Coordinated Research Project funded by the IAEA where the use of interim PET was investigated in order to risk stratify patients [9]. CD20 immunohistochemistry was performed for all of the cases for indication of anti CD20 therapy.…”
Section: Methodsmentioning
confidence: 99%
“…This method and markers are accepted as gold standard and reliable for the subclassification. These patients were a subset of the cohort of a Coordinated Research Project funded by the IAEA where the use of interim PET was investigated in order to risk stratify patients [9]. CD20 immunohistochemistry was performed for all of the cases for indication of anti CD20 therapy.…”
Section: Methodsmentioning
confidence: 99%
“…However, Mamot et al [26] analyzed 92 patients with DLBCL and reported a recurrence rate of 39.1% in patients with a negative interim PET-CT, which is similar to the recurrence rate of 30%-40% observed after treatment [27, 28]. In contrast, Carr et al [29] reported a recurrence rate of only 10% if the interim the PET-CT was negative. These differences may be attributed to different treatments, sensitivities of the tumor cells, histologies, stages, and completion times of the interim PET-CT examination [30] as completion of interim PET-CT in an interval of at least 3 weeks may reduce the proportion of false-negative results [31].…”
Section: Discussionmentioning
confidence: 84%
“…In some studies, iPET provided meaningful prognostic information (3,5,8,9), but in other studies, the end of treatment scan proved more informative (6,7,20). We previously (4) reported a low PPV of FDG iPET, at least in part resulting from rituximab-induced inflammation in the R-CHOP regimen (10) and from the use of iPET interpretation criteria that are now obsolete (12,21).…”
Section: Discussionmentioning
confidence: 99%